Securitisation and the bank lending channel - Yener Altunbas; Leonardo Gambacorta; David Marqués-Ibá\~nez (European Central Bank (ECB), 2007)
The dramatic increase in securitisation activity has odified the functioning of credit markets by reducing the fundamental role of liquidity transformation performed by financial intermediaries. We claim that the changing role of banks from “originate and hold” to “originate, repackage and sell” has also modified banks' abilities to grant credit and the effectiveness of the bank lending channel of monetary policy. Using a large sample of European banks, we find that the use of securitisation appears to shelter banks' loan supply from the effects of monetary policy. Securitisation activity has also strengthened the capacity of banks to supply new loans but this capacity depends upon business cycle conditions and, notably, upon banks' risk positions. In this respect, the recent experience of the sub-prime mortgage loans crisis is very instructive.
Keywords: E44; E55; 330; asset securitisation; bank lending channel; monetary policy; Verbriefung; Geldpolitik; Geldpolitische Transmission; EU-Staaten